Christopher Columbus & the new world - Sitko, Joseph (Colorado : Chariot [production company] ; Illinois : AGC/United Learning [distributor], 1999)
This program examines the life of Christopher Columbus and his role in world history
Narrator: Lois La Fond
Keywords: Columbus, Christopher; America -- Discovery and exploration